Non‐ischaemic dilated cardiomyopathy: recognising the genetic links. Issue 2 (21st September 2022) - Paul, Caitlin; Peters, Stacey; Perrin, Mark; Fatkin, Diane; Amerena, John
Abstract: The landscape of genetically related cardiac disease continues to evolve. Heritable genetic variants can be a primary cause of familial or sporadic dilated cardiomyopathy (DCM). There is also increasing recognition that genetic variation is an important determinant of susceptibility to acquired causes of DCM. Genetic forms of DCM can show a wide variety of phenotypic manifestations. Identifying patients who are most likely to benefit from genetic testing is paramount. The objective of this review is to highlight the importance of recognising genetic DCM, key genotype–phenotype correlations and the value of genetic testing in clinical management for both the individual and their family. This is likely to become more relevant as management strategies continue to be refined with genotype‐specific recommendations and disease‐modifying therapies.